A microfluidic device for simultaneous detection of enzyme secretion and elongation of a single hypha - Itani, Ayaka; Shida, Yosuke; Ogasawara, Wataru (Frontiers in Microbiology, 2023)
Filamentous fungi grow through elongation of their apical region by exocytosis and secrete commercially useful enzymes. Extensive branching of their hyphae and the inability to control environmental growth conditions are major impediments for the observation and analysis of a single hypha using conventional assays. Therefore, although hyphal morphology is closely linked to productivity, no real-time assessment of morphology and secreted exoenzymes have been carried out so far. In the present study, we developed a microfluidic system to compartmentalize a single hypha germinated from a single spore, enabling the observation of a single mycelium in detail. Furthermore, we have also developed a cellulase detection assay to detect hyphal growth and enzyme secretion in real time using Trichoderma reesei, a potent cellulase-producing hypha, as a model. A strong correlation was observed between growth and fluorescence intensity when fluorescence from the detection assay was compared with the GFP fluorescence intensity using a strain fused with cellulase cellobiohydrolase I and GFP. These results demonstrate that extracellular enzymes can be measured in real time and it assumes great significance as T. reesei is known to secrete a series of cellulases. This microfluidic system has enabled real-time visualization of hyphal and enzyme dynamics associated with carbon source exchange and quantitative gene expression dynamics. This technology can be applied to a wide range of biosystems, from bioenergy production to human health.